Seventh grave and no body - Jones, Darynda (Jones, Darynda. Charley Davidson, 2014)
"Twelve. Twelve of the deadliest beasts ever forged in the fires of hell have escaped onto our plane, and they want nothing more than to rip out the jugular of Charley Davidson and serve her lifeless, mangled body to Satan for dinner. So there's that. But Charley has more on her plate than a mob of testy hellhounds. For one thing, her father has disappeared, and the more she retraces his last steps, the more she learns he was conducting an investigation of his own, one that has Charley questioning everything she's ever known about him"--